Learning schools, learning systems - Clarke, Paul, 1961- (London ; New York : Continuum, 2000)
Using case studies, this text argues that the sensitivity of prevailing approaches to school improvements are causing reforms to fail to achieve their objectives. It proposes alternative methods of introducing change.
Series editors' foreword -- Acknowledgements -- Preface -- Pt. 1. Thinking about the journey ahead. 1. Searching for improvement ; 2. Changing the map: from schooling to learning ; 3. Moving from part to whole: from the instrumental to the sustainable ; 4. Finding the path -- Pt. 2. Living the journey. 5. Expeditions into learning: notes on establishing knowledge-generating and knowledge-using systems ; 6. A journey into learning -- Pt. 3. Seeing the journey. 7. Daring to tell the stories of the future ; 8. The great leap forward -- References -- Index.
Includes bibliographical references (p. 150-156) and index.
All Ages.
Keywords: School management and organization -- Great Britain; Educational change -- Great Britain; Educational innovations -- Great Britain